Seeking Positive Strengths in Buffering Athletes’ Life Stress–Burnout Relationship: The Moderating Roles of Athletic Mental Energy - Chiou, Shiow-Shya; Hsu, Yawen; Chiu, Yi-Hsiang; Chou, Chien-Chih; Gill, Diane L.; Lu, Frank J. (Frontiers in Psychology, 2020)
In search of positive strengths that bolster athletes’ reaction to stress, the purpose of this study was to examine the moderating effects of athletic mental energy on athletes’ life stress-burnout relationship. This study recruited two samples (Study 1= 230; Study 2 = 159) and administered the college student-athlete life stress (CSALSS, Lu et al., 2012), athletic mental energy (AMES, Lu et al., 2018), and athlete burnout questionnaire (ABQ, Raedeke & Smith, 2001). Two separate hierarchical multiple regression analyses found the emotional and cognitive components of athletic mental energy moderated athletes’ life stress-burnout relationship across two studies. Results provided the initial evidence that athletic mental energy can be positive strengths in buffering stress-burnout relationship. Theoretical implications, limitations, practical applications, and future research directions are discussed.